Exploring biodiversity in bael for healthy and wealthy life - Singh, A K; Singh, Sanjay; Singh, R S; Joshi, H K; Contractor, K (Indian Horticulture, 2015)
India is considered as national home of bael and having huge diversity in forest, cultivated farms, home backyard, premises of Lord Shiva temple, but the fast erosion of genetic resources is a cause of concern, hence the conservation of germplasm and creating awareness among the masses regarding its therapeutical and nutraceutical significance is essential for survival of existing genetic diversity and its utilization for wellbeing of mankind.